2011
DOI: 10.4103/0019-5049.89889
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Cormack and Lehane grading with laparoscopic assistance during tracheal intubation

Abstract: Background:To use laparoscope as an easily available and easy to use alternative option to videolaryngoscope.Aims:The aim of the study was to assess the improvement in the glottic view using a conventional direct laryngoscope (DL) assisted by a laparoscope with its endovision system along with the time taken for tracheal intubation.Settings and Design:A prospective, double blind, randomized, controlled study was conducted in a tertiary care centre.Methods:Sixty patients with American Society of Anesthesiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[ 3 4 10 11 ] Prior studies have demonstrated improved glottic visualisation with their use. [ 12 13 ] However, their performance has never been evaluated in comparison with commercially available videolaryngoscopes in a difficult airway scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 4 10 11 ] Prior studies have demonstrated improved glottic visualisation with their use. [ 12 13 ] However, their performance has never been evaluated in comparison with commercially available videolaryngoscopes in a difficult airway scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in CL views has also been demonstrated in multiple other studies. [ 12 14 15 ] The improvement in glottic view also explains the reduced requirement of laryngeal pressure and an increased lifting force with the use of videolaryngoscopes. Barak et al .…”
Section: Discussionmentioning
confidence: 99%